2020
DOI: 10.1101/2020.06.29.178202
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Valproic Acid-Induced Changes of 4D Nuclear Morphology in Astrocyte Cells

Abstract: AbstractHistone deacetylase inhibitors, such as valproic acid (VPA), have important clinical implications as human therapeutics and cellular reprogramming agents. They induce chromatin re-organization associated with changes in cell nuclear morphology. Current approaches aiming to quantify these changes so far have been limited to basic 2D measures. Here, we quantified changes in 3D nuclear morphology of primary human astrocyte cells treated with VPA for 7 days (hence, 4D). We … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Recently, a proposal was raised to study VPA-induced imaging changes in the nuclear morphology of astrocyte cells in a temporal context, a process that was named 4D morphometry (Kalinin et al, 2021). The authors reported results that reflected chromatin reorganization not only spatially but also temporally, which allowed them to conclude that their findings provided insights into the mechanisms of astrocyte-to-neuron reprogramming (Kalinin et al, 2021).…”
Section: Image Analysis Of Chromatin Suprastructural Changes Under Vpa Treatmentmentioning
confidence: 99%
“…Recently, a proposal was raised to study VPA-induced imaging changes in the nuclear morphology of astrocyte cells in a temporal context, a process that was named 4D morphometry (Kalinin et al, 2021). The authors reported results that reflected chromatin reorganization not only spatially but also temporally, which allowed them to conclude that their findings provided insights into the mechanisms of astrocyte-to-neuron reprogramming (Kalinin et al, 2021).…”
Section: Image Analysis Of Chromatin Suprastructural Changes Under Vpa Treatmentmentioning
confidence: 99%
“…While we hypothesize that cytoskeletal forces are the predominant mechanism leading to greater nuclear eccentricity, there could be additional factors that are causing these nuclear shape changes. For example, Kalinin and colleagues recently demonstrated that modulation of chromatin compaction with valproic acid treatment leads to changes in astrocyte nuclear shape [ 45 ]. We are currently investigating how these biomaterial conditions that induce TE-RMS formation affect the structure of the astrocyte nuclear lamina and chromatin arrangement to elucidate how they may contribute to astrocyte nuclear elongation.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that mechanical changes in nuclear morphology are often accompanied by changes in chromatin organization and gene expression which then lead to downstream alterations in cell activity and signaling [ 41 , 51 54 ]. However, there is limited research on how mechanically altering nuclear shape affects gene expression regulation and cell behavior in astrocytes specifically [ 44 , 45 ]. Overall, we performed a thorough structural evaluation of the intermediate filament cytoskeleton and nuclear morphology in TE-RMS astrocytes, revealing a novel astrocyte phenotype that has not previously been described in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…While measuring shape in 2D images has been illuminating, cells exist in 3D environments and their 3D geometry is a rich source of information about the inner workings of cells and tissues. For example, recent pioneering work has demonstrated that shape motifs extracted from 3D images can be linked to lipid membrane signalling and cancer signalling pathways [14], and changes in 3D nuclear morphometry are linked to chromatin organisation [18]. At the scale of developing tissues, the discovery of new 3D geometries has explained how cells pack stably into curved organs [19].…”
Section: Introductionmentioning
confidence: 99%